Ayakata The Mysterious Cripple - Nwachukwu-Agbada, J .Obii J (University Press Plc, 2013)
Umuibe, a sleeping rural habitation in Igboland, was jolted by a day of puzzling events when the unthinkable took place there$1! =s
Keywords: Juvenile Fiction